A new species of Franklinothrips Back (Thysanoptera: Aeolothripidae) from Yunnan, China - Mirab-Balou, Majid; Shi, Min; Chen, Xue-Xin (Zootaxa, 2011)
Species of the genus Franklinothrips Back are predators and ant-mimics, with the first two abdominal segments narrow and sometimes pale (Mound & Marullo, 1996), and an illustrated identification key to the 15 known species was provided by Mound & Reynaud (2005). A further new species was described recently from northern India (Vijay Veer, 2010), and these species have been found in the tropical areas of Asia, Africa, Central and South America, the Caribbean, Australia, and the southern United States. Previous studies on the genus include a key to six species from North America (Stannard, 1952), a key to six New World species (Mound & Marullo, 1996), and to two species from Europe (zur Strassen, 2003). From the Oriental region, species have also been described by Okajima (1997), and Reyes (1994).